A gendered analysis of shifts in adaptive water management in the Nile Delta of Egypt - Dessalegn, B.; Abd-Allah, Emman; Salem, S. A.; Swelam, A. (2021)
Understanding the logic behind farmers’ decisions to opt for specific adaptive water management practice is important to appreciate the challenges and opportunities they face, and to promote adoption of sustainable water management practices. This study considers gender, temporal, and spatial dimensions of water management that is juxtaposed at various scales. We adapt the Multi-Level Perspective (MLP) framework to our case and use it to contextualize key drivers of change within the micro, meso and macro levels of influence, and to demonstrate their individual as well as interactive effect on farmers’ decisions. We used qualitative data collected through Focus Group Discussions and Key Informant interviews to identify key drivers of change and farmers’ adaptive responses over time. Our findings show that farmers’ choices of adaptive water management are often collectively influenced by changes in the three spheres of influence and the interactions among them. The study highlights the importance of using MLP to identify major drivers of change that should be tackled to improve agricultural water delivery and use to achieve set targets for national food security.